2019
DOI: 10.1007/s10953-019-00905-y
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients of Concentrated Salt Solutions: A Monte Carlo Investigation

Abstract: Monte Carlo (MC) simulations were used to calculate single ion and mean ionic activity coefficients and water activity in concentrated electrolytes and at elevated temperatures. By using a concentration dependent dielectric constant, the applicability range of the MC method was extended to 3 mol·L −1 or beyond, depending on the salt. The calculated activity coefficients were fitted to experimental data by adjusting only one parameter, i.e., the cation radius. Fitted ionic radii obtained by such a procedure ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…58 Furthermore, they considered a concentration-dependent ε r with a polynomial function fitted to experimental data. In a more recent study, Abbas and Ahlberg 59 used MC simulations with the PM to calculate the IIACs and MIACs of several aqueous salts at elevated temperatures, with a concentration-dependent ε r , adopted from the study by Buchner et al 60 Although implicit-water simulations are computationally inexpensive, they do not include information on the solution structure and ion hydration. Despite obtaining reasonable agreement between MIAC values from implicit-water simulations and experiments, they typically underestimate the chemical potentials by several orders of magnitude.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Furthermore, they considered a concentration-dependent ε r with a polynomial function fitted to experimental data. In a more recent study, Abbas and Ahlberg 59 used MC simulations with the PM to calculate the IIACs and MIACs of several aqueous salts at elevated temperatures, with a concentration-dependent ε r , adopted from the study by Buchner et al 60 Although implicit-water simulations are computationally inexpensive, they do not include information on the solution structure and ion hydration. Despite obtaining reasonable agreement between MIAC values from implicit-water simulations and experiments, they typically underestimate the chemical potentials by several orders of magnitude.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, they considered a concentration-dependent ε r with a polynomial function fitted to experimental data. In a more recent study, Abbas and Ahlberg used MC simulations with the PM to calculate the IIACs and MIACs of several aqueous salts at elevated temperatures, with a concentration-dependent ε r , adopted from the study by Buchner et al…”
Section: Introductionmentioning
confidence: 99%
“…A second family of models is based upon the equation of state and includes, for example, the perturbed-chain-statistical-associated-fluid-theory. , In the conductor-like-screening-model with segment-activity-coefficients approach the molecular surface area is subdivided into charged segments that interact with each other . Recent studies have demonstrated that one can also use Monte Carlo and molecular dynamical modeling to calculate the activity and osmotic coefficients in NaCl solutions. …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this approach has the same limitation as that for the Gibbs ensemble MC method to be used in combination with atomistic force fields. Also, another straightforward approach used a modified Widom insertion method 81 to compute the activity coefficient of electrolyte, but in implicit water solvation making it unsuitable for atomistic force field either. Theoretical models based on experimental thermodynamic data are alternative approaches to predict vapor pressure (and, by extension, activity of water) in electrolyte solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%